Playstation Rental Business Development Strategy In The Digital Era - Rendra Prasetyo, Bagas; Abidin Riam, Zaenal; Farizie, Hamdan (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – This study aims to identify and analyze business development strategies for PlayStation rental services through digital transformation approaches, including online promotion, digital booking systems, and mobile application-based service integration. Design/Methodology/Approach – This study employs a quantitative research method with a descriptive approach. Data were collected from PlayStation rental business owners and customers in urban areas. The analysis focuses on evaluating the role of digital technology adoption in improving business operations, expanding market reach, and enhancing customer experiences. Findings – The results indicate that the adoption of digital technologies significantly improves market reach, operational efficiency, and customer experience in PlayStation rental businesses. Digital promotion strategies, online booking systems, and integrated digital services provide opportunities for businesses to adapt to changing consumer behavior and strengthen competitiveness in the entertainment service industry. Originality/Value This research is original in analyzing the impact of digital approaches, including online promotion, digital booking, and mobile app integration, on the business development of PlayStation rentals. The findings provide practical value by offering actionable insights for technology-based strategies that improve customer experience and business competitiveness in the digital era.